Fascial thickness and stiffness in hypermobile Ehlers‐Danlos syndrome. Issue 4 (6th November 2021) - Wang, Tina J.; Stecco, Antonio
Abstract: There is a high prevalence of myofascial pain in people with hypermobile Ehlers‐Danlos Syndrome (hEDS). The fascial origin of pain may correspond to changes in the extracellular matrix. The objective of this study was to investigate structural changes in fascia in hEDS. A series of 65 patients were examined prospectively—26 with hEDS, and 39 subjects with chronic neck, knee, or back pain without hEDS. The deep fascia of the sternocleidomastoid, iliotibial tract, and iliac fascia were examined with B‐mode ultrasound and strain elastography, and the thicknesses were measured. Stiffness (strain index) was measured semi‐quantitatively using elastography comparing fascia to muscle. Differences between groups were compared using one‐way analysis of variance. hEDS subjects had a higher mean thickness in the deep fascia of the sternocleidomastoid compared with non‐hEDS subjects. There was no significant difference in thickness of the iliac fascia and iliotibial tract between groups. Non‐hEDS subjects with pain had a higher strain index (more softening of the fascia with relative stiffening of the muscle) compared with hEDS subjects and non‐hEDS subjects without back or knee pain. In myofascial pain, softening of the fascia may occur from increase in extracellular matrix content and relative increase in stiffness of the muscle; this change is not as pronounced in hEDS.